PENGENALAN BAHASA INGGRIS PADA INDIVIDU AUTIS MELALUI GAMBAR BERSUARA - Diah Retno Anggraini; Titi Rachmi; Nargis Nargis (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
English has become the second language after Indonesian. This situation is used by education practitioners by incorporating English into their curriculum programs, for parents, English can affect children's competitiveness. Teaching and introducing English to autistic individuals is not easy. Talking photo is a learning media that is essay to apply because it can designed by the parents themselves and the contents can be adjusted to the needs. This research was conducted with qualitative methods describing the application of talking photo in introducing English. Respondents in this study were 3 autistic individuals of pre-school age, not yet exposed to English at all and did not enter the world of education or school. English in this study is vocabulary about parts of body and activities. The results obtained after two months of intensive exposure, respondent one could pronounce and respond to 7 parts of body vocabulary words and 4 activities vocabulary; second is able to pronounce and respond to 5 parts of body vocabulary words and 5 activities vocabulary and third is able to pronounce and respond to 3 parts of body and 3 activities vocabulary. Progress of autistic individuals occurs because of the integration of stimulus and family support.Keywords: Autistic Individual, English, Talking Photo